Sustainable energy and policy design on the energy transition to renewable energy systems in Stellenbosch, case study : Stellenbosch solar water heater by-law - Gosa, Thumakele (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.